Jews and journeys : travel and the performance of Jewish identity - Levinson, Joshua; Bashkin, Orit, 1974- (Jewish culture and contexts., 2021)
What happens when Jewish authors--whether by force or of their own free will, whether in reality or in the imagination--travel from one place to another? Jews and Journeys explores what it is about travel writing that enables it to become a central mechanism for exploring the realities and fictions of individual and collective identity.